Tourism observatories for monitoring MED destinations performance : the case of ShapeTourism project - Bertocchi, Dario (Array, 2020)
Following the precedent set by the Tourism Observatory (TO) run by the European Commission-DG GROW a few years ago, several initiatives have taken place to design and manage tourism observatories at both the transnational and local level. However, these initiatives do not yet seem able to provide adequate operational responses to the challenges that the Commission launched with the original TO. While the opportunities offered by the Web 2.0 still do not seem to have been sufficiently taken advantage of, such initiatives also have not yet developed suitable methodologies to operationally include the tourism industry in the studies and monitoring performed by the TOs. This work presents the lesion learnt from the ShapeTourism prototype including two different tools: an observatory with official and unofficial indicators, and a simulation tool to predict different scenarios and different sustainability levels, designed specifically to overcome the aforementioned limits. The prototype was tested in 2017 on the entire eligible area of ​​the 2014-2020 MED Programme covering 52 regions. The potentialities of this tool are shown through the creation on indicators, benchmarking and applications.